Gemini: desenvolvimento de concept art e artbook de personagens para uma narrativa Isekai - Dias, Gabriela Gonçalves [UNESP]; Tutui, Beatriz Arissa [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Este projeto tem como objetivo o desenvolvimento do concept art e artbook de seis personagens de uma história original que explora elementos do gênero isekai, utilizando técnicas e métodos do design gráfico para a idealização visual da narrativa. Para atingir esse objetivo foi realizada pesquisa bibliográfica sobre os temas isekai, sexualização, concept art, worldbuilding, além de uma análise de similares de artbooks, buscando maior compreensão sobre o processo de criação de personagens. Por fim foi possível criar a base narrativa de uma história original do gênero isekai, inserindo os conceitos de worldbuilding e concept art nos personagens.

This project aims to develop the concept art and artbook for six characters from an original story that explores elements of the Isekai genre, using graphic design techniques and methods for the visual development of the narrative. To achieve this goal, a bibliographic research was conducted on topics such as isekai, sexualization, concept art, worldbuilding, as well as an analysis of similar artbooks, in order to gain a deeper understanding of the character creation process. Finally, it was possible to create the narrative foundation for an original Isekai story, incorporating worldbuilding and concept art into the characters.
Gemini: development of concept art and character artbook for an Isekai narrative
Keywords: Concept art; Isekai; Character design; Sexualização feminina; Character design; Female sexualization